Trends and Prospects of Change in Wheat Self-Sufficiency in Egypt - Ahmed Abdalla; Till Stellmacher; Mathias Becker (Agriculture, 2022)
Egypt is the largest wheat importer in the world; however, it produces only half of the 20 million tons of wheat that it consumes annually. The population of Egypt is currently growing by 1.94% per year, and projections predict that the demand for wheat will be nearly doubled by 2050. Russia and Ukraine are major wheat exporters to Egypt and globally, shipping grains from ports in the Black Sea. The ongoing conflict aggravates the already precarious food security situation in Egypt and many other import-dependent countries in Africa and Asia by disrupting supplies and accelerating food price hikes. Wheat is a strategic commodity in Egypt. Its production is a question of political stability. Against this backdrop, the Egyptian government declared gaining wheat self-sufficiency as a strategic aim. This study provides an overview of the degree and trends of cultivated wheat area, yield, production, and wheat self-sufficiency in Egypt between 2000 and 2020, followed by a qualitative analysis determining external pressures and system-immanent drivers that had an impact on wheat self-sufficiency in the past two decades in view of predicting future pathways to achieve wheat self-sufficiency in a sustainable way. The study underlines some critical external pressures such as agricultural policies, (subsidized) production inputs, climate conditions, global wheat supply chains, and system-immanent drivers such as domestic wheat supply prices and yields influencing the area of wheat cultivation and its productivity. There is a significant need to implement more effective and long-term sustainable agricultural policies in order to make wheat production in Egypt (more) attractive and feasible for smallholders again.